Impact of Macroeconomic Policieson Income Distribution : An Empirical Study. (IMF Working Papers; Working Paper, 1988)
There has been a growing awareness of the income distribution dimension of macroeconomic policies. This paper presents a framework for studying this issue empirically, and considers the case of the Philippines using data available from integrated surveys of households. After developing and estimating an analytical model, it was found that underemployment, inflation, and government spending worsen income distribution, while productivity gains, the real interest rate, and the real exchange rate were found to be progressive instruments.